2022
DOI: 10.3389/fphar.2022.973611
|View full text |Cite
|
Sign up to set email alerts
|

S-3′-hydroxy-7′, 2′, 4′-trimethoxyisoxane, a novel ferroptosis inducer, promotes NSCLC cell death through inhibiting Nrf2/HO-1 signaling pathway

Abstract: Background: Ferroptosis is a newly discovered and promising non-apoptotic programmed cell death (PCD), and inducing ferroptosis in cancer cells could open up a novel avenue for drug screening and cancer therapy. S-3′-hydroxy-7′, 2′, 4′-trimethoxyisoxane (ShtIX), a new isoflavane compound, has been reported to possess cytotoxicity in non-small cell lung cancer (NSCLC). The aim of this research is to explore the ShtIX-induced cell death form and its underlying molecular mechanism in NSCLC cells.Methods: Cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…HO-1, an important source of cellular iron ions, plays a key role in erastin induced cell ferroptosis by inducing the peroxidation of cell membrane lipids, which causes cells to undergo ferroptosis. There have been numerous studies showing that Nrf2 can suppress ferroptosis by increasing the expression of target genes related to iron and ROS metabolism including HO-1 [ 15 , 16 ]. Moreover, exosome treatment enhanced the ability of cell invasion and clonogenicity, and the transfection of si-GOT1 reversed the effect of exosomes, but in the effect of NK-252, the ability of tumor cell invasion ( Figure 7 B) and clonogenicity ( Figure 7 C) was again enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…HO-1, an important source of cellular iron ions, plays a key role in erastin induced cell ferroptosis by inducing the peroxidation of cell membrane lipids, which causes cells to undergo ferroptosis. There have been numerous studies showing that Nrf2 can suppress ferroptosis by increasing the expression of target genes related to iron and ROS metabolism including HO-1 [ 15 , 16 ]. Moreover, exosome treatment enhanced the ability of cell invasion and clonogenicity, and the transfection of si-GOT1 reversed the effect of exosomes, but in the effect of NK-252, the ability of tumor cell invasion ( Figure 7 B) and clonogenicity ( Figure 7 C) was again enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…This activation enhances the antioxidant capacity, drug resistance, invasion, and metastasis of tumor cells [31]. Studies have consistently reported a substantial up-regulation of Nrf2 expression across diverse malignancies, encompassing ovarian cancer, head and neck cancer, lung cancer, and breast cancer [36][37][38][39]. Consequently, the inhibition of Nrf2 activity holds substantial potential in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[63] Furthermore, acetaminophen and a novel ferroptosis inducer, S-3'-hydroxy-7', 2', 4'-trimethoxyisoxane, were both shown to promote NSCLC cell death by inhibiting the NRF2/heme oxygenase-1 (HO-1) signaling pathway. [64,65] The E3 ligase mind bomb 1 (MIB1) also promotes the proteasomal degradation of NRF2 and enhances the ferroptosis sensitivity in lung cancer. [66] In summary, individualized treatment for lung cancer patients should be developed based on the genetic mutation status of KEAP1/NRF2.…”
Section: Nrf2mentioning
confidence: 99%